2007
DOI: 10.1111/j.1741-3737.2007.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Grandparents in Single‐Mother Families

Abstract: This article examines whether children living with single mothers benefit when they also live with a grandparent, using data from the 1979 to 2002 waves of the National Longitudinal Survey of Youth merged mother‐child file (N = 6,501). Results indicate that for White children, living with a single mother and a grandparent is associated with increased cognitive stimulation and higher reading recognition scores, compared to living with a single mother alone. For Black children, grandparent coresidence is associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 25 publications
4
65
0
Order By: Relevance
“…In contrast, studies using more 116 the ANNALS oF the AMeRICAN ACADeMy robust techniques to address selection into coresidential situations (Augustine and Raley 2013;Dunifon and Kowaleski-Jones 2007) find evidence that African American children do not derive benefits from three-generational living arrangements.…”
Section: Three-generational Familiesmentioning
confidence: 87%
See 1 more Smart Citation
“…In contrast, studies using more 116 the ANNALS oF the AMeRICAN ACADeMy robust techniques to address selection into coresidential situations (Augustine and Raley 2013;Dunifon and Kowaleski-Jones 2007) find evidence that African American children do not derive benefits from three-generational living arrangements.…”
Section: Three-generational Familiesmentioning
confidence: 87%
“…If this is the case, estimates of the associations between three-generational arrangements and individual or family well-being will be biased. Very few studies have addressed this issue; exceptions include Dunifon and Kowaleski-Jones's (2007) use of a child fixed-effects design, and Augustine and Raley's (2013) propensity score analysis. Future work in this area should strive to employ rigorous research designs to address the selection of families into living arrangements.…”
Section: Three-generational Familiesmentioning
confidence: 98%
“…Race and ethnicity are strongly associated with socioeconomic and cultural factors that promote grandparental coresidence, with or without parents present (e.g., Stykes, Manning, and Brown 2014;Rossi and Rossi 1990). In addition to racial disparities in exposure to grandparental coresidence (e.g., Ellis and Simons 2014), race and ethnicity are also important moderators of linkages between grandparental coresidence and child well-being (Dunifon and Kowaleski-Jones 2007;Pilkauskas 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on three generational households have shown mixed results on the effect of grandparental presence on child well-being (e.g., Deleire & Kalil, 2002;Dunifon & Kowaleski-Jones, 2007). One key factor explaining this is the varying age of the grandchildren and, as a consequence, the age of grandparents.…”
Section: Introductionmentioning
confidence: 97%